Effect of Earthquake loads on School Buildings in the Kingdom of Saudi Arabia - Yasser Alashker; Khalid Elhady; Mohammed Ismaeil (Civil Engineering Journal, 2019)
Background: The designing of the reinforced concrete building for the reduction of the seismic load has significantly gained popularity. Most of the buildings in Saudi Arabia are designed for the gravity load, based on its seismicity level. Objective: The study evaluates the effects of the earthquake load on the RC school building located in Saudi Arabia. Method: An equivalent static analysis technique used to apply the seismic analysis and design method according to Saudi Building Code SBC301 (2007). This design code is used to redesign the chosen school building. The SAP 2000 structural analysis software was used to analyses and study the structure behaviour due to the seismic load. Results: The results of the study provide that the RC school building design in Saudi Arabia is inadequate, and unsafe for the earth quakes. Conclusion: One of the important conclusions in this study is that the designer of the school building in Saudi Arabia should take into consideration the earthquake loads. It also emphasizes on the development of the adequate framework for the implementation of the safe designing of the buildings inclusive of earthquake safety measures.